Media observatories as instruments of media literacy teaching - Herrera Damas, Susana (2007)
There is little doubt. In spite of the fact that we all live in the so called Network society, tradicional systems do That is why tradicional spaces for formal education should be completed by o ther actors which con tribute to media literacy teachjng. One of them is the media observatory, a recent but growing realiry in Latín America. The objective of this arcicle is describing the peculiariry of this mechanism and specifying the instruments that allow this formarive rask. First, we will make a brief reference of media literacy teaching need